Narrative and ethics. An analysis of the usage of literary tradition by Aristotle - Pena Mardaras, M.ª Cristina (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In recent years, there has been a growing interest in narrative in the field of Ethics. This fact is especially relevant within Neo-Aristotelianism. This paper explores the usage of literary tradition by the philosopher in the Nicomachean Ethics and analyses the resulting data according to the categorization of literary genres in the Poetics. The aim is to identify the function assigned by Aristotle to narrative in ethical reflection and to justify the relevance of tragedy as the consummate expression of the condition of human life.